PROBLEMATIKA TANAH BEKAS EIGENDOM VERPONDING YANG DIGUNAKAN OLEH DEBITUR SEBAGAI JAMINAN KEPADA KREDITUR - zain (Program Studi Hukum Universitas Pamulang, 2025)
This research examines the legal problems arising from the use of former eigendom verponding land, a legacy of colonial law, as collateral in loan agreements between debtors and creditors. The historical background of the status of this land, which has not been fully consolidated within the national agrarian legal system post-independence, often creates legal uncertainty. The main problems arise when land with eigendom verponding status is used as credit collateral, encompassing aspects such as the validity of ownership, procedural obstacles in the process of converting and registering rights, difficulties in legally and effectively encumbering it with Mortgage Rights, up to the potential for disputes and difficulties in execution should the debtor default due to differing interpretations or incomplete administrative documents. This study aims to deeply analyze the legal aspects that cause vulnerability in collateral transactions involving this land object and its significant impact on legal certainty. Using a normative legal research method with a statutory and conceptual approach, this study identifies related norms and practices to provide a comprehensive overview of the complexity of this issue and its implications. It is expected that the findings of this research can contribute to efforts towards creating stronger legal certainty in the practice of providing credit with former eigendom verponding land as collateral.